Protective role against hydrogen peroxide and fibroblast stimulation via Ce-doped TiO2 nanostructured materials - Gravina, Noel (2016)
Background: Cerium oxide (CeO2) and Ce-doped nanostructured materials (NMs) are being seen as innovative therapeutic tools due to their exceptional antioxidant effects; nevertheless their bio-applications are still in their infancy. Methods: TiO2, Ce–TiO2 and CeO2–TiO2 NMs were synthesized by a bottom-up microemulsion-mediated strategy and calcined during 7 h at 650 °C under air flux. The samples were compared to elucidate the physicochemical characteristics that determine cellular uptake, toxicity and the influence of redox balance between the Ce3 +/Ce4 + on the cytoprotective role against an exogenous ROS source: H2O2. Fibroblasts were selected as a cell model because of their participation in wound healing and fibrotic diseases. Results: Ce–TiO2 NM obtained via sol–gel reaction chemistry of metallic organic precursors exerts a real cytoprotective effect against H2O2 over fibroblast proliferation, while CeO2 pre-formed nanoparticles incorporated to TiO2 crystalline matrix lead to a harmful CeO2–TiO2 material. TiO2 was processed by the same pathways as Ce–TiO2 and CeO2–TiO2 NM but did not elicit any adverse or protective influence compared to controls. Conclusions: It was found that the Ce atoms source and its concentration have a clear effect on material's physicochemical properties and its subsequent influence in the cellular response. It can induce a range of biological reactions that vary from cytotoxic to cytoprotective. General significance: Even though there are still some unresolved issues and challenges, the unique physical and chemical properties of Ce-based NMs are fascinating and versatile resources for different biomedical applications.